PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PROBING- PROMPTING UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK - Cici Maria Putri; Elva Yasmi; Erviyenni Erviyenni (Jurnal Pendidikan Kimia Universitas Riau, 2020)
The research has been conducted at SMAN 5 Pekanbaru which aims to improve student learning achievement on the subject of ion stoichiometry in class X MIPA. This type of research is an experimental study with adesign Randomized Control Group pretest-posttest.. The sample from the study was students of class X MIPA 3 as an experimental class. The experimental class is the class applied to the type Probing-Prompting type cooperative learning model. The data analysis technique used is the t-test. Based on the results of the data analysis test, tcount> ttable is 3,59> 1.67, with value of its influence to student learning achievement is15,56%. It can be concluded that the application of Probing-Prompting type cooperative learning model can improve student learning achievement on the subject of ion stoichiometry in class X MIPA of SMA Negeri 5 Pekanabru with value of its influence to student learning achievement is 15,56%.